Around the clock: unveiling giraffe rest-activity rhythms and social dynamics - Mebus, Hanna; Schneider, Sebastian; Dierkes, Paul Wilhelm; Burger-Schulz, Anna Lena (Frontiers in Conservation Science, 2024)
Understanding the daily activity patterns and social dynamics of giraffes (Giraffa camelopardalis) is crucial for their management and conservation. In this study, a comprehensive 24-hour observational analysis of three female reticulated giraffes kept for four weeks at the Opel-Zoo in Kronberg, Germany, was conducted. Using infrared-sensitive cameras, the study captured behavioral data across baseline and two intervention phases involving changes in group composition. During the day, the giraffes exhibited a high level of activity, primarily engaging in walking, standing, and feeding behaviors.Diurnal resting was minimal, with sporadic lying phases. Night-time behavior was markedly different, with the giraffes spending most of the night lying down, interspersed with periods of feeding. The presence of a male giraffe during one intervention phase significantly altered diurnal activity patterns, increasing standing behaviors and decreasing feeding time. Social interactions, including nearest neighbor preferences, varied across day and night periods and changed with alterations in group composition. The study highlights the complexity of giraffe social dynamics and their adaptation to different social contexts. These findings provide valuable insights into the natural behavioral rhythms and social behaviors of giraffes, which are essential for effective zoo management and conservation strategies.